MAḤMÛD ABÛ RAYYAH DAN KRITISISME HADIS - Anam, Wahidul (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
Maḥmûd Abû Rayyah comes to the study of ḥadîth as a controversial scholar. His criticism has made a significant change in modern period in which his critics are directed towards some literatures and early ḥadîth scholars (râwî). One of the making polemic in his study is his critical study on the authenticity of ḥadîth in Bukhârî’s book, Ṣahîḥ Bukhârî. It is not only Bukhârî whom his critics are pointed out, but also Abû Hurayrah, a person who has narrated so many ḥadîth and become the most cited name in ḥadîth literatures. This paper would shed light on the epistemological view of Abû Rayyah in ḥadîth criticism. It highlights three branches of ḥadîth studies: authenticity, reliability and historical analysis. This study suggests that Abû Rayyah put al-sunnah al-hudâ (a living tradition of Muḥammad which is related to ‘aqîdah and sharî‘ah) as a main tool for validity to determine the authenticity of ḥadîth. In this case, every ḥadîth which contradicts to this value should be rejected. Further he said that ḥadîth codification did not take place in the period prior to al-Zuhrî. The political pressure is one of the reasons why al-Zuhrî and other Muslims are militant to write and collect Muḥammad traditions of ḥadîth.